C.S. Lewis and the Christian life: living the faith today - Cain, Clifford Chalmers (Lexington Books, 2021)
"Inspired by the person and writings of C.S. Lewis, this book examines pertinent and pressing issues in living the Christian faith today. Experts in their fields share their insights and conclusions"--